Pengaruh Profitabilitas, Likuiditas, dan Leverage Terhadap Pengungkapan Corporate Social Responsibility (Studi Empiris pada Perusahaan yang Terdaftar di Indeks SRI KEHATI Tahun 2014-2018): Keywords: CSR, Disclosure; Profitability; Liquidity; Leverage - Sugeng Firdausi; Wanda Amelia Prihandana (Jurnal Akuntansi, 2022)
CSR disclosure in an annual report or a separate report is a tool for management to communicate with stakeholders regarding information on corporate social responsibility that has been implemented. The purpose. of this research is to examine. the effect of profitability, liquidity, and leverage, simultaneously and partially on CSR disclosure. The .population of this study. are companies .listed in the SRI KEHATI stock index in. 2014-2018. The sampling. technique used was. purposive. sampling .method and the research sample was obtained as many as 22 companies. The  data  used  is  .secondary data in annual .reports. The. analytical method .used is. multiple linear regression. analysis .with SPSS 25 software. The results show that .profitability, liquidity, and .leverage simultaneously influence CSR disclosure. Partially, profitability and liquidity have no effect on CSR. disclosure. Meanwhile, leverage .has a partial effect on CSR .disclosure.